The role of volatile compounds and genes that involved in ester biosynthesis during strawberry fruit (Fragaria × ananassa Duchesne) development - Mokhtari Shojaee, Fahimeh (Acta agriculturae Slovenica, 2025)
Strawberry (Fragaria × ananassa Duchesne) is one of the most crucial berry fruits because of its nutrients and pleasant taste. The present research is to identify volatile com-pounds, study the biosynthesis pathway during three develop-mental stages, and insilico analysis of lipoxygenase (LOX), alcohol dehydrogenase (ADH), and alcohol acyltransferase (AAT) genes in strawberries. The results indicated that 68 volatile compounds were identified in different developmental stages. The gas chromatography/mass spectrometry showed that the amounts of esters increased during the development of strawberry fruit, while aldehydes and alcohol components decreased during the red stage. The results showed LOX gene expression decreased during fruit development, while ADH and AAT gene expression increased in ripe fruit. It seems that alcohols have a minor contribution to producing the aroma of fruits due to early consumption. Furthermore, esters in the red stage play a significant role in the aroma of ripe fruit. The knowledge of the phytochemical profile of strawberries in the growing stages could be used in different applications of these materials in var-ious fields, including food, medical, and pharmaceutical industries, and production of food essences and natural flavorings, as well as fragrance design.
Keywords: alcohols; aldehidi; aldehydes; alkoholi; cikel lipoksigenaze; esters; estri; lipoxygenase pathway; plod jagodnjaka; strawberry fruit